Sub-Lethal Effects of Bifenthrin and Imidacloprid on Megacephala carolina carolina L. (Coleoptera: Carabidae) in Turfgrass - Shimat V. Joseph (Insects, 2022)
The tiger beetle, Megacephala carolina carolina L. (Coleoptera: Carabidae), is a common predator in turfgrass and ornamental landscapes in Georgia, USA. Among insecticides used in turfgrass to control foliar and root-feeding insect pests, bifenthrin and imidacloprid are routinely used. It was unclear whether sub-lethal doses of bifenthrin and imidacloprid could cause nontarget effects on larvae and M. carolina carolina adults. Thus, the objective was to determine the sub-lethal effects of bifenthrin and imidacloprid on larvae and M. carolina carolina adults. The results show that M. carolina carolina larvae actively hunt for passing prey by waiting at the hole of the tunnel during the day and nighttime. This larval behavior was affected by sub-lethal doses (up to 25% of full label rate) of bifenthrin but not of imidacloprid. The walking behavior of adult M. carolina carolina was also altered when exposed to sub-lethal doses of bifenthrin as they traveled further distances at greater velocities than the nontreated control. The results imply that turfgrass managers should avoid treating lawns where tiger beetles have actively colonized.